Materialism, Social Formation and Socio-Spatial Relations : an Essay in Marxist Geography - Peet, Richard (Cahiers de géographie du Québec, 1978)
Marxist geography is a part of marxist science and as such it has the relative autonomy of the instances of the societal whole studied. These instances or the relations between instances which are the object of marxist geography are first the dialectical relation between social formations and the natural world and second the spatial dialectic between components of a social formation embedded into space or between social formations in different regions. Hence the need to refer to the concepts of mode of production and of social formation and to define and illustrate the concept of spatial dialectic and the development of contradictions in space.